Cyber bullying: A legal framework for South African educators - Moodley, Isabel (Southern African Public Law, 2023)
In South Africa, the conduct of learners is regulated by certain provisions in the South African Schools Act, specifically section 8 which authorises the school governing body to ‘adopt a code of conduct for learners after consultation with learners, educators and parents’. The rationale of a code of conduct is to establish a ‘disciplined and purposeful school environment, dedicated to the improvement and maintenance of the quality of the learning process’. Bullying or peer victimisation (as it is sometimes referred to in South Africa) opposes this rationale and is fast becoming an ever increasing problem for schools and educators all over the world, including South Africa.